Phénoménologie et marxisme Perspectives historiques et legs théoriques - Vincenzo d'Alfonso, Matteo; Moreau, Pierre-François (La croisée des chemins, 2021)
The links between Marxism and phenomenology were a fundamental axis of the European cultural debate in the 1960s and 1970s. In post-war France, Sartre and Merleau-Ponty already referred, in terms of theoretical foundation, to the phenomenological tradition of Husserl and Heidegger, and in terms of civil engagement, to Marxism. As early as 1951, Trần Đức Thảo, a student of Merleau-Ponty's, established a first synthesis of these two paradigms in his Phenomenology and Dialectical Materialism. Eleven years later, Jean-Toussaint Desanti returned to the demand for a convergence between phenomenology and Marxism. Other attempts emerged first in Italy and then in Germany. The aim of this volume is to propose a synthesis on the subject. It also aims to promote an initial historical reflection on the philosophical current which, for at least two decades, has occupied the intellectual scene, and to evaluate its legacy in contemporary debate.